1993
DOI: 10.1038/hdy.1993.101
|View full text |Cite
|
Sign up to set email alerts
|

Models for the evolution of selfing under alternative modes of inheritance

Abstract: In an approach that explicitly incorporates genetic changes over consecutive generations of selffertilization, we contrast the effect of different modes of inheritance for selfing rate upon the evolutionary equilibrium selfing rate. A monotonic decline of fitness with consecutive generations of selfing was assumed. We found the range of conditions permitting evolutionarily stable mixedmating systems to increase with the number of genes controlling the selfing rate. When the mating system is controlled by a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 39 publications
(26 reference statements)
1
27
0
Order By: Relevance
“…Based on their model of the coevolution of mating systems and inbreeding depression, Schultz and Willis (1995) concluded that associations between mating system and viability loci may not be detectable when mating system modifiers have only small quantitative effects on selfing rates. Similarly, Latta and Ritland (1993) have demonstrated the mode of inheritance of mating-system determinants has a large effect on equilibrium predictions, with multilocus inheritance promoting more favorable conditions for mixed mating. Clearly the theory needs to be expanded to include multilocus determination of selfing rates as well as multilocus fitness determinants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their model of the coevolution of mating systems and inbreeding depression, Schultz and Willis (1995) concluded that associations between mating system and viability loci may not be detectable when mating system modifiers have only small quantitative effects on selfing rates. Similarly, Latta and Ritland (1993) have demonstrated the mode of inheritance of mating-system determinants has a large effect on equilibrium predictions, with multilocus inheritance promoting more favorable conditions for mixed mating. Clearly the theory needs to be expanded to include multilocus determination of selfing rates as well as multilocus fitness determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Species (Dole and Ritland 1993;Carr and Dudash 1996) and populations (Latta and Ritland 1993) of Mimulus that have higher selfing rates have lower inbreeding depression than those that are more outcrossing, a pattern common in flowering plants (Husband and Schemske 1996). What is not known is whether these current associations were initially responsible for driving the evolution of selfing in their ancestral populations (Holsinger 1991;Uyenoyama and Waller 1991a,b).…”
mentioning
confidence: 99%
“…4. Latta and Ritland (1993) showed that mixed mating can be stable for selfing diploids when there is a monotonical decline in fitness for serial inbreeding. We followed a similar strategy to Damgaard et al (1992) to show mixed mating may be stable for selfing diploids.…”
Section: Resultsmentioning
confidence: 98%
“…He showed that mixed mating systems could evolve as pure inbreeding or outbreeding populations were not resistant against opposite strategies invading. In support, Latta and Ritland (1993) showed, using recursive equations for multiple loci, that a decline in fitness of serial inbred individuals led to stable mixed mating. They found that mixed mating evolved at higher frequencies when controlled by increasing numbers of genes.…”
Section: Introductionmentioning
confidence: 83%
“…The genetic basis of the mating system-that is, the number of loci and levels of dominance-has been shown to affect the evolutionary outcome of selection in some models of mating system evolution (Charlesworth and Charlesworth 1990;Latta and Ritland 1993). For instance, Latta and Ritland (1993) showed that, under some conditions, mixed mating systems can be evolutionarily stable and that this outcome is more likely when many genes control the rate of selfing.…”
mentioning
confidence: 98%